Investigating the Competencies and Skills of Computer Professionals - Gonçalves, Rodrigo Feitosa; Passos, Odette Mestrinho; Amorim, Rainer Xavier de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2024)
Context: The role of the computing professional is considered crucial in organizations. This professional career requires a range of competencies and skills to support organizations in strategic decisions related to information technology (IT). A computing professional performs specific functions, such as software development and project management, intending to achieve the organization’s objectives. Problem: The lack of clarity regarding the nature and set of competencies and skills required of a computing professional can negatively impact the performance of related activities and, consequently, the training of qualified professionals. Solution: We investigated a set of competencies and skills required of computing professionals for education/training purposes. IS theory: The work was developed using the Social Learning Theory perspective. This theory explains how people think and what factors determine their behavior. Method: We conducted a Multivocal literature review and an opinion poll with 53 participants (students) for Bachelor’s degrees in Computer Science, Computer Engineering, Information Systems, and Software Engineering, as well as a Degree in Computer Science. Results: The nature of the competencies and skills of computing professionals are hard skills and soft skills, which include building hardware, language skills, programming/software development, complex problem-solving, and working in a team. Contributions and Impact in the IS area: The article’s main contribution is to make a product possible for any organization/university or individual to develop the competencies and skills of computing professionals. This study also contributes to the Grand Research Challenge “Strengthening the Sociotechnical Approach in Information Systems Research”.